2022
DOI: 10.1186/s12871-022-01613-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic individualized PEEP guided by driving pressure in laparoscopic surgery on postoperative atelectasis in elderly patients: a prospective randomized controlled trial

Abstract: Background Driving pressure (ΔP = Plateau pressure-PEEP) is highly correlated with postoperative pulmonary complications (PPCs) and appears to be a promising indicator for optimizing ventilator settings. We hypothesized that dynamic, individualized positive end-expiratory pressure (PEEP) guided by ΔP could reduce postoperative atelectasis and improve intraoperative oxygenation, respiratory mechanics, and reduce the incidence of PPCs on elderly patients undergoing laparoscopic surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The LUS can be used to quantitatively evaluate changes in pulmonary ventilation during the perioperative period [16][17][18][19][20][21][22]. This study showed that setting individualized PEEP according to driving pressure can reduce the LUS 30 min after surgery, improves oxygenation before extubation, and has a lung-protection effect, which is consistent with the results of previous studies [23].…”
Section: Discussionsupporting
confidence: 87%
“…The LUS can be used to quantitatively evaluate changes in pulmonary ventilation during the perioperative period [16][17][18][19][20][21][22]. This study showed that setting individualized PEEP according to driving pressure can reduce the LUS 30 min after surgery, improves oxygenation before extubation, and has a lung-protection effect, which is consistent with the results of previous studies [23].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, VT and PEEP are only associated with the development of PPCs if they result in a change in driving pressure. The results of several randomized controlled studies 12 , 22 , 23 have demonstrated that a driving pressure-guided ventilation strategy is superior to a conventional LPVS in reducing the incidence of PPCs. One study 24 showed a 3.4% increase in the incidence of major morbidity in patients for every 1 cm H 2 O increase in driving pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PPCs within three days after surgery was recorded (three or more new findings: cough, increased sputum, dyspnea, chest pain, temperature > 38 °C, and heart rate > 100 beats/min). 12 …”
Section: Methodsmentioning
confidence: 99%
“…A recent retrospective cohort analysis 24 Accordingly, recent prospective studies demonstrated that PEEP optimization guided by DP is associated with a lower incidence of PPCs in both thoracic and abdominal surgery 2,25 . For elderly patients undergoing laparoscopic surgery 26 , DP-guided individualized PEEP has reduced lung atelectasis at the end of surgery and 15 min after admission to PACU. The intraoperative respiratory mechanics have also been improved.…”
Section: Discussionmentioning
confidence: 99%